ANALISIS KONDISI FISIK DOMINAN ACADEMY UTAMA RAYA - shalihin, muhammad rayyis (UNIB Press, 2025)
This study aims to analyze the dominant physical condition of young players at Academy Utama Raya, with a primary focus on four physical components: speed, endurance, agility, and explosive power. The study employs a quantitative descriptive method using purposive sampling on 20 athletes aged 13–14 years. Data were collected through a series of physical tests, including the 30-meter sprint test, Illinois Agility Test, Standing Broad Jump, and Pacer Test. The results show that explosive power and speed are the two most dominant physical components among the participants, while agility and endurance fall into the moderate to low categories. These findings have important implications for coaches in designing more balanced training programs to enhance overall physical performance. The study also emphasizes the importance of early physical development to support optimal athletic growth in the future.